2022
DOI: 10.1136/bjsports-2021-105059
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic partial meniscectomy versus physical therapy for traumatic meniscal tears in a young study population: a randomised controlled trial

Abstract: ObjectiveTo compare outcomes from arthroscopic partial meniscectomy versus physical therapy in young patients with traumatic meniscal tears.MethodsWe conducted a multicentre, open-labelled, randomised controlled trial in patients aged 18–45 years, with a recent onset, traumatic, MRI-verified, isolated meniscal tear without knee osteoarthritis. Patients were randomised to arthroscopic partial meniscectomy or standardised physical therapy with an optional delayed arthroscopic partial meniscectomy after 3-month f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…For longer-term outcomes, both surgical and nonsurgical treatments are effective. Two RCTs of 121 and 100 young adults (mean age, 30-35 years) compared early surgery (arthroscopic partial meniscectomy or meniscal repair) with 12 weeks of exercise therapy (neuromuscular exercises 1-2 times weekly) with the option of surgery later if needed. Both RCTs found that both groups experienced clinically relevant improvements in pain and function with no clinically important differences between groups .…”
Section: Meniscal Tearsmentioning
confidence: 99%
See 2 more Smart Citations
“…For longer-term outcomes, both surgical and nonsurgical treatments are effective. Two RCTs of 121 and 100 young adults (mean age, 30-35 years) compared early surgery (arthroscopic partial meniscectomy or meniscal repair) with 12 weeks of exercise therapy (neuromuscular exercises 1-2 times weekly) with the option of surgery later if needed. Both RCTs found that both groups experienced clinically relevant improvements in pain and function with no clinically important differences between groups .…”
Section: Meniscal Tearsmentioning
confidence: 99%
“…Two RCTs of 121 and 100 young adults (mean age, 30-35 years) compared early surgery (arthroscopic partial meniscectomy or meniscal repair) with 12 weeks of exercise therapy (neuromuscular exercises 1-2 times weekly) with the option of surgery later if needed. Both RCTs found that both groups experienced clinically relevant improvements in pain and function with no clinically important differences between groups . In both RCTs, patients with severe displaced tears (ie, locked knee indicative of displaced bucket-handle tear) and those associated with an anterior cruciate ligament rupture were excluded, as these cases typically have more aggravating symptoms and require surgery.…”
Section: Meniscal Tearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meniscal tears in young adults have typically been treated with arthroscopic surgery. Recently, two randomised trials comparing early meniscal surgery to exercise therapy and education with optional delayed surgery (if needed) reported clinically relevant improvements in patient-reported outcomes (PROMs) for both treatment strategies, with negligible between-group differences 1 2. Furthermore, in the two trials, many patients randomised to exercise (84% at 12 months and 59% at 24 months) did not undergo surgery during follow-up 1 2…”
Section: Introductionmentioning
confidence: 99%
“…We cannot ignore the evidence: At this point, about a dozen welldesigned, randomized controlled trials confirm that fact [3,9,10,12,13,26,27,28,32], and I can find only one RCT [5]-a problematic study for reasons I've described before [14]that suggests anything different. Evidence from two recent randomized trials has even questioned its use among younger patients, excluding those who present with locking [29,31]. This puts the onus on those who think the operation helps to prove it.…”
mentioning
confidence: 99%